Nanoscale metal-organic frameworks for mitochondria-targeted radiotherapy-radiodynamic therapy. Issue 1 (December 2018) - Ni, Kaiyuan; Lan, Guangxu; Veroneau, Samuel; Duan, Xiaopin; Song, Yang; Lin, Wenbin
Abstract Selective delivery of photosensitizers to mitochondria of cancer cells can enhance the efficacy of photodynamic therapy (PDT). Though cationic Ru-based photosensitizers accumulate in mitochondria, they require excitation with less penetrating short-wavelength photons, limiting their application in PDT. We recently discovered X-ray based cancer therapy by nanoscale metal–organic frameworks (nMOFs) via enhancing radiotherapy (RT) and enabling radiodynamic therapy (RDT). Herein we report Hf-DBB-Ru as a mitochondria-targeted nMOF for RT-RDT. Constructed from Ru-based photosensitizers, the cationic framework exhibits strong mitochondria-targeting property. Upon X-ray irradiation, Hf-DBB-Ru efficiently generates hydroxyl radicals from the Hf6 SBUs and singlet oxygen from the DBB-Ru photosensitizers to lead to RT-RDT effects. Mitochondria-targeted RT-RDT depolarizes the mitochondrial membrane to initiate apoptosis of cancer cells, leading to significant regression of colorectal tumors in mouse models. Our work establishes an effective strategy to selectively target mitochondria with cationic nMOFs for enhanced cancer therapy via RT-RDT with low doses of deeply penetrating X-rays. Photosensitizers delivered to mitochondria of cancer cells can enhance photodynamic therapy. Here, the authors report mitochondria-targeted radiation therapy and radiodynamic therapy of colorectal cancer models with a cationic nanoscale metal-organic framework to overcome shallow light penetration of Ru-based photosensitizers.